2002
DOI: 10.1108/01437730210429070
|View full text |Cite
|
Sign up to set email alerts
|

The impact of executive coaching and 360 feedback on leadership effectiveness

Abstract: Does executive coaching really work? Does it help improve leadership effectiveness and productivity? This action research study answers these questions by tracking the progress of 281 executives participating in a six‐month coaching and 360 feedback process. The results suggest that the combination of multi‐rater feedback and individual coaching do increase leadership effectiveness up to 60 per cent ‐‐ according to direct report and peer post‐survey feedback. Implications of the results for future executive de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
0
15

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 20 publications
8
118
0
15
Order By: Relevance
“…This finding is consistent with the study of Thach (2002) in which coaching helps people in achieving the goals set for improving organisational productivity and personal satisfaction. Similarly, Bandura and Cervone (1986) also concluded that coaching is considered as a form of social persuasion in which people are guided by recommendations to believe they can successfully cope with the given tasks.…”
Section: Discussion and Research Implicationsupporting
confidence: 82%
“…This finding is consistent with the study of Thach (2002) in which coaching helps people in achieving the goals set for improving organisational productivity and personal satisfaction. Similarly, Bandura and Cervone (1986) also concluded that coaching is considered as a form of social persuasion in which people are guided by recommendations to believe they can successfully cope with the given tasks.…”
Section: Discussion and Research Implicationsupporting
confidence: 82%
“…The empirical studies published on executive coaching have mainly been concerned with its ability to generate positive effects. In short, the results of the reported studies indicate that executive coaching in an organizational setting is positively and significantly linked to individual performance (McGovern et al, 2001;Olivero, Bane, & Kopelman, 1997;Smither et al, 2003), self-efficacy (Baron & Morin, 2007;Evers et al, 2006), organizational commitment and performance (Luthans & Peterson, 2003;Olivero et al, 1997), leadership (Thach, 2002), and conflict resolution (McGovern et al, 2001). These studies also report interesting relationships with intangible variables such as the learner' s self-awareness and satisfaction with supervisors and colleagues (Luthans & Peterson, 2003;Styhre, 2008), work satisfaction (Luthans & Peterson, 2003;McGovern et al, 2001), balance between personal and professional lives, as well as time management (Gegner, 1997).…”
Section: Executive Coachingmentioning
confidence: 99%
“…However, many authors have noted the lack of scientific studies on the process and the outcome of executive coaching (see Lowman, 2005;Sue-Chan & Latham, 2004), and others have argued that this development approach is overused considering the paucity of research on the subject (McGovern et al, 2001). In short, the results from empirical studies indicate that executive coaching is positively associated with self-efficacy (Baron & Morin, 2007;Evers, Brouwers, & Tomic, 2006), leadership (Thach, 2002) (Smither, London, Flautt, Vargas, & Kucine, 2003). In regard to the process, very little is known about the variables that influence its effectiveness.…”
mentioning
confidence: 99%
“…The discussions of results did, however, provide some additional insights into the contributions of different aspects of coaching to perceived program success. For example, a study by Thach (2002) of 281 executives, found that the combination of multi-rater feedback and individual coaching do increase leadership effectiveness up to 60% according to direct report and peer post-survey feedback.…”
Section: Methodological Approachmentioning
confidence: 99%
“…Support for the coachee included empathy (De Haan, Culpin, & Curd, 2011;Gregory & Levy, 2011) being non-judgemental (Blackman, 2010;Judge & Cowell, 1997), and being able to put issues into a larger perspective (Ahern, 2003;Graham et al, 1994;Orenstein, 2006;Styhre & Josephson, 2007). Communication skills were particularly important (Graham et al, 1994;Longenecker, 2010;Rekalde et al, 2015;Thach, 2002) with particular significance attached to the provision of clear performance expectations (Ahern, 2003;Graham et al, 1994;Orenstein, 2000) and detailed and regular feedback (De Haan, 2008b;Graham et al, 1993Graham et al, , 1994Gregory & Levy, 2011;Judge & Cowell, 1997;Karsten, 2010;Longenecker, 2010;Miller, 2003;Olivero et al, 1997;Orenstein, 2006;Strayer & Rossett, 1994;Taie, 2011;Wasylyshyn, 2003). In the case of these first three themes the conclusions are consistent with those made by Joo (2005) and Passmore and Fillery-Travis (2011).…”
Section: Characteristics and Behaviours Of Effective Coachesmentioning
confidence: 99%